2015
DOI: 10.5194/acp-15-2889-2015
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric and mesospheric HO<sub>2</sub> observations from the Aura Microwave Limb Sounder

Abstract: Abstract. This study introduces stratospheric and mesospheric hydroperoxyl radical (HO 2 ) estimates from the Aura Microwave Limb Sounder (MLS) using an offline retrieval (i.e. run separately from the standard MLS algorithm). This new data set provides two daily zonal averages, one during daytime from 10 to 0.0032 hPa (using day-minus-night differences between 10 and 1 hPa to ameliorate systematic biases) and one during nighttime from 1 to 0.0032 hPa. The vertical resolution of this new data set varies from ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 49 publications
4
25
0
Order By: Relevance
“…It is found that the satellite data of the HO 2 distribution regularly demonstrate lower altitudes of this component's mesospheric maximum. These results confirm the ones obtained via the offline retrieval of HO 2 from the MLS primary data (Millán et al, 2015).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is found that the satellite data of the HO 2 distribution regularly demonstrate lower altitudes of this component's mesospheric maximum. These results confirm the ones obtained via the offline retrieval of HO 2 from the MLS primary data (Millán et al, 2015).…”
Section: Introductionsupporting
confidence: 88%
“…Nighttime equilibrium in the NO 2 -NO 3 -N 2 O 5 system is used to determine surface layer N 2 O 5 concentration, equilibrium constant of this system, equilibrium partitioning between NO 3 and N 2 O 5 , and loss coefficients of NO 3 , N 2 O 5 , and NO x (Martinez et al, 2000;Brown et al, 2003;Crowley et al, 2010;McLaren et al, 2010;Benton et al, 2010;Sobanski et al, 2016). Platt et al (1979) Ko et al (2003), Cantrell et al (2003), and Penkett et al (1997Penkett et al ( , 1998 algebraic expressions derived from equilibrium conditions for H 2 O 2 , peroxy radicals, and nitrogen species were used to determine equilibrium values of peroxide concentration, total peroxy radical level, and NO/NO 2 ratio, and to diagnose the ozone production and loss levels in a clean or polluted troposphere.…”
Section: Introductionmentioning
confidence: 99%
“…The impacts on other retrieved parameters are negligible. Given the proposed design of the instrument (Murtagh, 2016), the 1-year frequency variability may be relatively large (> 0.5 MHz or 250 m s −1 ), and we should consider that an absolute frequency knowledge, good enough for retrieving winds, may not be available. Frequency calibration will be performed using short-term wind retrieval bias estimates within 40-60 km where other systematic errors are small.…”
Section: Retrieval Methodsmentioning
confidence: 99%
“…The second proposal is the Stratospheric Inferred Winds (SIW) instrument. It is a small and low-cost satellite instrument being studied as part the Swedish InnoSat program (Lindberg, 2016;Murtagh, 2016). This program has planned to launch a scientific instrument every 2 years, and SIW has been selected for the second launch near 2022.…”
Section: Introductionmentioning
confidence: 99%
“…4-6 of the range above 0.046 hPa diminishes the mismatch for OH and O 3 but not for HO 2 . An 332 algorithm for offline retrieval of daily zonal means of HO 2 using averaged MLS radiances was 333 performed by Millán et al (2015). The product of the algorithm, the alternative dataset of night-time 334 and daytime HO 2 , recently became available at https://mls.jpl.nasa.gov.…”
mentioning
confidence: 99%